Educational resilience and knowledge building - Sousa, Carolina Silva (2014)
The article discusses academic resilience, with an emphasis on the construction of mathematical communication as a result of processes of social interaction among students and teachers. It is an educational dynamics which resulted in a growing appreciation and recognition of students’ mathematical knowledge, framing the primordial role of new strategies and forms of learning. In this framework, the researchers, based on the interpersonal relationships, empathy, social skills and sense of belonging to a group on the interface with the social and emotional resilience, highlight the importance of positive experiences to generate feelings of self-efficacy, self-esteem and academic success, contributing to help students and teachers to cope with the changes and adaptations to new learning situations.